PENGARUH PENDEKATAN MINDFUL LEARNING PARTICIPATION TERHADAP KEMAMPUAN METAKOGNITIF SISWA PADA MATA PELAJARAN AKIDAH AKHLAK KELAS VIII DI MTS SUMBERSARI KOWANG - Luluk Iddah Masrufah; Achoita, Ana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this research is the low metacognitive ability of students in learning Akidah Akhlak. The purpose of this study is to determine how the Mindful Learning Participation approach affects the metacognitive ability of eighth grade students (VIII) at MTs Sumbersari Kowang. The methodology used is a quantitative approach with a descriptive correlational design. By using a saturated sampling technique, namely between the control class and the experimental class. Researchers collected data with a questionnaire, and normality tests, homogeneity, Pearson Product Moment correlation, and independent sample t-test and paired t-test. The results showed that the data were normally distributed and homogeneous. With a significance level (0.520) and a correlation coefficient of (-0.132), in the control group which did not show a clear relationship. In contrast, in the experimental class a positive and significant relationship was obtained with a correlation coefficient (0.472) and a significance level (0.011) which was smaller than (0.05). Therefore, students' metacognitive skills improved in the experimental class between the pretest and posttest. According to the t-test results, which also showed a significant difference between the control and experimental classes. Therefore, it can be said that the Mindful Learning Participation strategy significantly influences the improvement of students' metacognitive skills. This approach is effective in increasing students' learning awareness, active participation, and ability to regulate, monitor, and assess their learning process.